HUMAN MACHINE INTERFACE DESIGN OF INDUSTRIAL AUTOMATED MACHINE USING SIMATIC SCADA SYSTEM - Meddeb, Houda; Abdellaoui, Zouhaira; Ezzine, Olfa (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
In an industrial world full of technological advancements where competitiveness is the essential objective, automation has become a fundamental necessity to achieve higher productivity with less chance of error in a limited time. Additionally, regular monitoring of processes is required to improve system performance and ensure employee safety. In this paper, a method for realizing an automated weighing and bagging machine is proposed, and special emphasis is placed on the weighing system. A simulated process prototype based on a SCADA (Supervisory Control and Data Acquisition) system and PLC (Programmable Logic Controller) of weighing and bag packing machines is designed to fill and close bags with the product. Operators can monitor the process and control outputs through the HMI (Human Machine Interface) screen.